Effect of Copper Doping on Optical and Structural Properties of sprayed Tin Oxide Thin Films - Benhaoua Taha; Benhaoua Atmane; Benhaoua Boubakeur; Rahal Achour (University Of Eloued جامعة الوادي, 2020)
In this paper, Effect of doping with copper on optical and structural properties of tin oxide (SnO2) thin films was investigated. the effect. SnO2 as transparent conductive oxide (TCO) was prepared using spray pyrolysis technique. Optical and structural properties of the product were investigated using UV-Vis spectrometry and XRD techniques. It was observed that the thin films have a high transmittance in visible range: 80% transmittance at undoped state and increased by copper doping to reach 84.8% at 0.6% level. The band gap energy ranges from 3.925 to 3.965 eV. It increases, with slight fluctuation, upon doping level increasing. Crystalline structure of thin films grew preferably along the (211) plan on a tetragonal system. Lattice parameter a has increased to a maximum value at 0.2% doping, and then decreased beyond. Unit cell volume followed the same trend as lattice parameter a. Similarly, the grain size of crystallite increases to a maximum at 0.2% doping, and then decreases with further doping. As results height quality thin films with high transmittance and regular thickness were obtained.
Intervention
Keywords: Thin films; Tin oxide; TCOs; Copper doping; XRD